Cover Picture: Simultaneous and Selective Imaging of Dopamine and Glutamate Using an Enzyme‐modified Large‐scale Integration (LSI)‐based Amperometric Electrochemical Device (Electroanalysis 12/2018). Issue 12 (10th December 2018) - Abe, Hiroya; Iwama, Tomoki; Yabu, Hiroshi; Ino, Kosuke; Inoue, Kumi Y.; Suda, Atsushi; Kunikata, Ryota; Matsudaira, Masahki; Matsue, Tomokazu
Abstract : The cover picture shows simultaneous and selective electrochemical Imaging of two neurotransmitters. By using enzyme‐modified large‐scale integration (LSI)‐based amperometric devices, simultaneous and selective imaging of dopamine and glutamate was achieved. More details are discussed in the short communication by Hiroya Abe, Tomoki Iwama, Hiroshi Yabu, Kosuke Ino, Kumi Y. Inoue, Atsushi Suda, Ryota Kunikata, Masahki Matsudaira, and Tomokazu Matsue. DOI:10.1002/elan.201800386